2022
DOI: 10.1002/fsn3.2793
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Romanov breed lamb gender on carcass traits and meat quality parameters including biogenic amines and malondialdehyde changes during storage

Abstract: The present study aims to evaluate the effect of Romanov breed lamb gender on carcass traits and meat quality parameters, as well as on the formation of biogenic amines (BAs) and malondialdehyde during meat storage. Obtained results revealed that lamb gender had a significant influence on sternum/breastbone, ribs, right shoulder, and bones of the back leg. Significantly higher lightness (by 3%) was found for male meat; however, higher redness of female meat was observed (by 7.7%). In all cases, a lower pH was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
0
5
1
Order By: Relevance
“…LM is a source of essential FAs, especially linolenic (C18:3 cis-6,9,15), eicosapentaenoic (C20:5 n 3), and docosahexaenoic (C22: 6 𝑛 − 3) acids, which have positive influences on cardiovascular disease prevention [ 138 , 139 ]. Moreover, the ratio of PUFA/SFA is very important and can vary from 0.06 [ 14 , 19 , 140 , 141 ] to 0.59 [ 142 , 143 , 144 ] in LM, according to various researchers. Our findings are in agreement with the abovementioned results because we found that the PUFA/SFA ratio in the treated LM samples was 0.1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LM is a source of essential FAs, especially linolenic (C18:3 cis-6,9,15), eicosapentaenoic (C20:5 n 3), and docosahexaenoic (C22: 6 𝑛 − 3) acids, which have positive influences on cardiovascular disease prevention [ 138 , 139 ]. Moreover, the ratio of PUFA/SFA is very important and can vary from 0.06 [ 14 , 19 , 140 , 141 ] to 0.59 [ 142 , 143 , 144 ] in LM, according to various researchers. Our findings are in agreement with the abovementioned results because we found that the PUFA/SFA ratio in the treated LM samples was 0.1.…”
Section: Resultsmentioning
confidence: 99%
“…LM contains essential amino and fatty acids, as well as micronutrients (e.g., Fe, Zn, and Se, as well as vitamins B3 and B12 and folic acid) [ 2 , 9 , 10 ], which play important roles in human nutrition [ 7 , 11 ]. However, LM consumption is restricted by its specific odour, taste, texture, and short shelf life [ 7 , 12 , 13 , 14 ]. Different technologies have been applied to improve LM quality parameters, e.g., sonication [ 15 , 16 ] and thermal processing [ 7 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…DC, delayed chilling; RC, rapid chilling; MT, milk teeth; TT, two teeth. Age, sex, and chilling effects from male carcasses lost more weight during cooking than meat from female carcasses, which was also seen in lambs (Klupsaite et al, 2022). This occurred mainly due to differences in pHu values which were lower in female lambs, and fatness level which was higher in females, although WBSF values were similarly unaffected by sex (Facciolongo et al, 2018).…”
Section: Cooking Loss (%)mentioning
confidence: 87%
“…Sample preparation and determination of BA content in pork meat samples were performed according to the method of Ben-Gigirey et al [ 41 ], with some modifications [ 42 ]. The BAs were extracted with 0.4 mol/L perchloric acid, and dansyl chloride solution in acetonitrile (10 mg/mL) was used as a derivatisation reagent.…”
Section: Methodsmentioning
confidence: 99%